2020
DOI: 10.1007/s00281-020-00794-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards new TB vaccines

Abstract: Mycobacterium tuberculosis remains the leading cause of death attributed to a single infectious organism. Bacillus Calmette-Guerin (BCG), the standard vaccine against M. tuberculosis, is thought to prevent only 5% of all vaccine-preventable deaths due to tuberculosis, thus an alternative vaccine is required. One of the principal barriers to vaccine development against M. tuberculosis is the complexity of the immune response to infection, with uncertainty as to what constitutes an immunological correlate of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 237 publications
(265 reference statements)
0
26
0
1
Order By: Relevance
“…In the last two decades, significant progress has been made in the search for a better vaccine against TB [ 19 , 20 , 21 , 22 , 23 , 24 ]. Table 1 provides an overview of the main TB vaccine candidates currently in clinical development and reports their composition.…”
Section: Vaccines In Tb: Current Statusmentioning
confidence: 99%
“…In the last two decades, significant progress has been made in the search for a better vaccine against TB [ 19 , 20 , 21 , 22 , 23 , 24 ]. Table 1 provides an overview of the main TB vaccine candidates currently in clinical development and reports their composition.…”
Section: Vaccines In Tb: Current Statusmentioning
confidence: 99%
“…Conversely, a limited protective effect was observed against pulmonary TB, especially in adults, which is not only the most prevalent form of the disease but also the principal source of transmission [ 10 ]. Epidemiological evidence highlighted that the BCG degree of protection varies geographically [ 6 , 7 , 8 , 11 , 12 , 13 , 14 , 15 ], while several studies suggested a lower and short-lasting BCG protection in people previously sensitized with Mtb and non-tuberculous mycobacteria (NTB) [ 7 , 11 ]. Additionally, it has an unfavorable risk profile in immunocompromised conditions, for example, congenital immunodeficiencies and HIV infections, because of BCG bacteremia that follows vaccination [ 9 , 13 ].…”
Section: Bcg: a Cornerstone In Tb Handlingmentioning
confidence: 99%
“…Mtb infection is a complex, multi-stage process that generally arises after the inhalation of Mtb -containing aerosolized droplets released from people with active pulmonary TB ( Figure 1 ). The respiratory tract and bronchoalveolar spaces represent a unique immunological compartment where the innate immune system and the respiratory epithelium act as the first barrier to providing early clearance of the pathogen [ 11 , 16 , 17 , 18 , 19 ]. Following initial exposure to Mtb , a small percentage of exposed humans can quickly clear the infection.…”
Section: Tuberculosis Immunopathologymentioning
confidence: 99%
“…Furthermore, the immune responses induced by cross-reactive antigens due to exposure to environmental mycobacteria lead to an early clearance of antigens in the BCG vaccine, which prevents an effective immune response from being generated, rendering it a failure, and hence causing a blocking effect [ 21 , 22 , 23 , 24 ]. The use of M. tuberculosis -specific antigens as subunit vaccines is expected to overcome the problems of blocking or masking effects [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…BCG vaccination also faces a problem in the diagnosis of TB by using the widely used antigenic preparation of M. tuberculosis known as the purified protein derivative (PPD), in the tuberculin skin test, due to the presence of the cross-reactive antigens [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. It is expected that M. tuberculosis -specific antigens may overcome the problem of diagnostic inaccuracy associated with the use of PPD in BCG-vaccinated people [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%